История формирования и изучения лапидарной эпиграфической коллекции Одесского археологического музея НАН Украины - Охотников, С.Б. (Материалы по археологии Северного Причерноморья, 2009)
The basic stages of forming and studying of epigraphical lapidary collection of OAM are examined in the article. This largest collection of Ukraine counts about 230 copies of inscriptions. The inscriptions were found in the ancient cities of the North and Western Black Sea coast, in the territory of actual Italy, Greece, on the islands of the Aegean Sea etc. The forming of this unique collection began about 200 years ago and the process goes on.